Analisis Penerapan Manajemen dalam UMKM di Era Digital - Clodia Trisintia Bela; Kholilul Kholik; Melisa Avsary Purba; Yofi Ananda Sitorus; Lola Karisma; Dea Amelia Putri; Marsella Grasia Hutabarat (Pusat Riset dan Inovasi Nasional, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, particularly in job creation and improving community welfare. The rapid development of information technology in the digital era presents both opportunities and challenges for MSMEs in managing their businesses. The implementation of proper management is a crucial factor in improving MSME performance and competitiveness in an increasingly competitive business environment. This study aims to analyze the implementation of management functions, including planning, organizing, actuating, and controlling, in MSMEs in the digital era. The research method used is a descriptive qualitative approach with a literature study, by reviewing various books, scientific journals, and regulations related to management and MSMEs. The results indicate that the implementation of management in MSMEs in the digital era has not been optimal. This can be seen from weak business planning, unclear division of tasks, and simple control systems. However, the use of digital technology such as social media and online marketplaces has had a positive impact on MSME development. With proper management implementation and optimal utilization of digital technology, MSMEs are expected to improve business performance and ensure business sustainability.